RELIGIOUS EXCLUSIVITY AND ITS SOLUTIONS IN UNIVERSITAS ISLAM INDONESIA YOGYAKARTA - Purwanto, Muhammad Roy (International Journal of Psychosocial Rehabilitation, 2020)
Some research has found that the level of exclusivity of students and educators inIndonesia has increased significantly. The increase in the exclusivism in Indonesia indicates that the educational institutions have the opportunity to be a propagation and antidote to exclusivism even radicalism. The university through its policy of religious development and its lecturer has a significant role in the cultivation of characters and religious understanding of students who are more open minded and tolerant. This research aims to look the program of de-radicalization and de-exclusivity religious understanding of students at the Islamic University of Indonesia Yogyakarta. This research is a qualitative-descriptive field study. The population of this research is a student, lecturer, and leader of the Faculty of Islamic Sciences, University Islam Indonesia. Data collection is conducted with semi-structured interviews and documentation. The results showed that the faculty of Islamic Sciences, University Islam Indonesia has carried out the de-radicalization of religious understanding of his students, both programmatic and incidental. Programmatic de-radicalization is through classroom learning and religious coaching in extracurricular activities. While an incidental de-radicalization is done through curricular activities, studies, religious coaching, ta’lim and recite.